2016
DOI: 10.1074/jbc.m116.749812
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Changes in the Oligomeric State of a Candidate Endoplasmic Reticulum (ER) Ceramide Sensor by Single-molecule Photobleaching

Abstract: Edited by George CarmanSingle-molecule photobleaching has emerged as a powerful non-invasive approach to extract the stoichiometry of multimeric membrane proteins in their native cellular environment. However, this method has mainly been used to determine the subunit composition of ion channels and receptors at the plasma membrane. Here, we applied single-molecule photobleaching to analyze the oligomeric state of an endoplasmic reticulum (ER) resident candidate ceramide sensor protein, SMSr/SAMD8. Coimmunoprec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Sphingomyelin synthase-related protein (SMSr) is a six-transmembrane protein in the endoplasmic reticulum (ER), which generates DG and ceramide phosphoethanolamine (CPE) by utilizing phosphatidylethanolamine (PE) and ceramide ( Figure 4 ) [ 269 ]. A SAM domain in SMSr form a homo-oligomer [ 270 , 271 ]. DGKδ also possesses a SAM domain and forms homo-oligomers via the domains [ 112 , 113 ].…”
Section: Dg-providing Pathway Upstream Of Dgkmentioning
confidence: 99%
See 1 more Smart Citation
“…Sphingomyelin synthase-related protein (SMSr) is a six-transmembrane protein in the endoplasmic reticulum (ER), which generates DG and ceramide phosphoethanolamine (CPE) by utilizing phosphatidylethanolamine (PE) and ceramide ( Figure 4 ) [ 269 ]. A SAM domain in SMSr form a homo-oligomer [ 270 , 271 ]. DGKδ also possesses a SAM domain and forms homo-oligomers via the domains [ 112 , 113 ].…”
Section: Dg-providing Pathway Upstream Of Dgkmentioning
confidence: 99%
“…DGKδ also possesses a SAM domain and forms homo-oligomers via the domains [ 112 , 113 ]. Intriguingly, the SAM domains in SMSr and DGKδ are primary structurally similar to each other [ 270 , 271 ]. It is noteworthy that we recently found that SMSr and DGKδ interacted with each other through their SAM domains ( Figure 4 ) [ 272 ].…”
Section: Dg-providing Pathway Upstream Of Dgkmentioning
confidence: 99%
“…By controlling the ratio of PEGs graft to the lysine moieties of PLL, 30% of the ε-amine moieties in poly-L-lysine are conjugated with PEG-OPSS and the remaining are left unmodified for electrostatic interaction. Such PEG-tolysine ratio yields high biocompatibility while maintaining sufficient amine density to warrant stable adsorption onto glass substrates [36][37][38].…”
Section: Resultsmentioning
confidence: 99%
“…Dynamic changes in the stoichiometry of membrane proteins are hard to resolve by bulk biochemical approaches like chemical crosslinking or co-immunoprecipitation analysis. Therefore, our ongoing efforts focus on the application of single-molecule fluorescence microscopy as complementary method to monitor SMSr oligomerization in intact cells52.…”
Section: Discussionmentioning
confidence: 99%